1963
DOI: 10.1037/h0047831
|View full text |Cite
|
Sign up to set email alerts
|

Conforming behavior and personality variables in college women.

Abstract: Conforming behavior of 41 college freshman women, as measured in an Asch situation, was compared with the scales of the Edwards Personal Preference Schedule, the Gough California Psychological Inventory, and the Gordon Personal Profile. In the sample studied, only the Edwards' Abasement scale was able to generate a small but significant relationship (+ .33) with a kind of behavior which should have been predictable from some 12 to perhaps 27 of the 38 measures used. Excepting the 5 scales of Cough's 18, on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1967
1967
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The individual differences (sex) factor was insignificant. 0 Our interpretation of conformity would be congruent with that of Appley and Moeller (1963) and Moeller and Applezweig (1957), who suggest that conformity is situationally bound and is a means to an end rather than a personality variable. Work now in progress is aimed at determining the relative influence of situational (reinforcement) and personality factors on conformity.…”
Section: Discussionsupporting
confidence: 82%
“…The individual differences (sex) factor was insignificant. 0 Our interpretation of conformity would be congruent with that of Appley and Moeller (1963) and Moeller and Applezweig (1957), who suggest that conformity is situationally bound and is a means to an end rather than a personality variable. Work now in progress is aimed at determining the relative influence of situational (reinforcement) and personality factors on conformity.…”
Section: Discussionsupporting
confidence: 82%
“…Some other investigators who have concluded that conformity operates as a means to an end are Kelman (1950), McDavid (1959, Endler (1966), Kimbrell and Blake (1958), Lanzetta (1958, 1960b), Moeller and Applezweig (1957), Wiener et al (1956), Stone (1967), and Appley and Moeller (1963).…”
Section: The Supply Sidementioning
confidence: 99%
“…Recent work has, however, suggested that the relationship between these two variables may be nonmonotonic (Cox & Bauer, 1964; Gergen & Bauer 3 ). Indeed, a study reported by Appley and Moeller (1963) shows that 33 of 38 personality variables were nonmonotonically related to persuasibility, even within a rather homogeneous population.McGuire * (1966, in press) has suggested a multiplicative two-factor model to account for these nonmonotonic relations between personality variables and susceptibility to social influence. Briefly, it is postulated that opin-1 The authors wish to acknowledge valuable contributions made by William J. McGuire to all phases of this study.…”
mentioning
confidence: 97%
“…Recent work has, however, suggested that the relationship between these two variables may be nonmonotonic (Cox & Bauer, 1964; Gergen & Bauer 3 ). Indeed, a study reported by Appley and Moeller (1963) shows that 33 of 38 personality variables were nonmonotonically related to persuasibility, even within a rather homogeneous population.…”
mentioning
confidence: 97%